Financial literacy as mediating factors affecting the financial performance of MSMEs in digital cities and special economic zones in 3T regions - Miran, Michael; Evinita, Lenny; Pesak, Pricilia Joice (Edelweiss Applied Science and Technology, 2025)
The Disadvantaged, Frontier, and Outermost (3T) regions are parts of Indonesia that, as a whole, have less developed social, economic, geographical, and cultural conditions compared to other regions throughout Indonesia. The financial performance of Micro, Small, and Medium Enterprises (MSMEs) in the 3T regions needs to be improved so that the sustainability of MSMEs as a contributor to Indonesia's economic growth can be guaranteed. The purpose of this quantitative research is to examine how accounting applications, internal perspectives, external perspectives, marketplace, and financial literacy in MSMEs in 3T areas correlate with each other. In addition, this study also investigates the mediating impact of financial literacy. A survey was conducted on 28 MSME players in North Lembeh Sub-district, Bitung City. For analysis, the SmartPLS statistical analysis technique was also used. This study found that the limitations that exist in the 3T areas make accounting applications, internal perspectives, external perspectives, and marketplaces, both directly and mediated by financial literacy, have no impact on the financial performance of MSMEs.